(untitled) (Biological Sciences - PJSIR, 2007)
Pakar wood ( Ficus Lacon Buch) of particle size 0.315-1 .00 mm was subjected to organosol v delignification with acetic, formic and propion ic acids. Optimum deligni fication was achieved with 95, 80 and 70% of these acids, respectively, with opti mum catalyst (HCI) concentration of0.25, 0.20 and 0.15%, the ti me bei ng 1 80, 1 20 and 1 20 mi n, respectivel y.